2019
DOI: 10.3835/plantgenome2018.06.0045
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐Wide Analysis and Prediction of Resistance to Goss's Wilt in Maize

Abstract: Core Ideas Goss's wilt is a complex, polygenic trait with no resistance genes or large‐effect QTL. Genomic prediction accuracy of 0.69 achieved for Goss's wilt in panel of diverse inbred lines. Association mapping using a diverse panel of maize lines revealed no significant SNPs. Goss's bacterial wilt and leaf blight is one of the most important foliar diseases of maize (Zea mays L.). To date, neither large‐effect resistance genes, nor practical chemical controls exist to manage the disease. Thus, the import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 79 publications
(102 reference statements)
3
16
0
Order By: Relevance
“…Thus, if there is a pleiotropic gene underlying these regions, the mechanism is not obviously associated with pathogen kingdom or the growth of the pathogen in the vasculature. Resistance to all five of the diseases examined here is largely quantitative ( Qiu et al 2020 ; Cooper et al 2019 ; Wisser et al 2006 ), and thus it is conceivable that common quantitative disease resistance mechanisms could underlie the observed multiple disease resistance. Several mechanisms have been hypothesized to underlie quantitative disease resistance ( Poland et al 2009 ; Yang et al 2017a ) and some of these could have effects across pathogen kindgoms and pathogenesis strategies.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Thus, if there is a pleiotropic gene underlying these regions, the mechanism is not obviously associated with pathogen kingdom or the growth of the pathogen in the vasculature. Resistance to all five of the diseases examined here is largely quantitative ( Qiu et al 2020 ; Cooper et al 2019 ; Wisser et al 2006 ), and thus it is conceivable that common quantitative disease resistance mechanisms could underlie the observed multiple disease resistance. Several mechanisms have been hypothesized to underlie quantitative disease resistance ( Poland et al 2009 ; Yang et al 2017a ) and some of these could have effects across pathogen kindgoms and pathogenesis strategies.…”
Section: Discussionmentioning
confidence: 95%
“…Disease resistance introgression line population DRIL78 is an ideal CSSL population for multiple disease evaluation, as the donor parent (NC344) is multiple disease resistant and the recurrent parent (Oh7B) is multiple disease susceptible ( Lopez-Zuniga et al 2019 ; Cooper et al 2019 ; Qiu et al 2020 ; Wisser et al 2011 ). The population was developed by a cross between NC344 and Oh7B, three generations of backcrosses, and four subsequent generations of self-pollinating via single-seed descent to obtain BC 3 F 4:5 lines ( Lopez-Zuniga et al 2019 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…SNPs are mostly used because of their stability and abundance in the genome [ 30 ]. They have been widely used in plants to evaluate genetic diversity, construct linkage maps, and association analysis [ 31 , 32 ]. However, studies have shown that joint analysis of molecular and morphological data provides in-depth insight into population structure and genetic diversity, and this has been used in different crops [ 33 , 34 , 35 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Higher prediction accuracies of 0.706 (dent) and 0.690 ( int) in estimating the GEBVs were reported based on the training set size for NCLB resistance[48]. Average prediction accuracies based on genomic data were also high for a complex trait like grain yield (0.72-0.74)[49], grain moisture (0.90)[50,51], Goss's wilt (0.69)[52], Gray leaf spot (0.84)[53], Fusarium ear rot (0.46) and fumonisin contamination (0.67)[54], Fusarium ear rot (ranging from 0.34 to 0.4)[55], and maize chlorotic mottle virus (0.32, 0.78, 0.47 and 0.21) [56] in maize. Higher prediction accuracies of 0.72 and 0.80 were reported for different agronomic traits in sugar beet[57].…”
mentioning
confidence: 99%